Gamma rays and thermal neutron attenuation studies of special composite mixes for using in different applications. (September 2021) - Abdelmonem, A.M.
Abstract: Lead borate glass and unglazed ceramic composites have been investigated as shielding against gamma rays and thermal neutron. Attenuation parameters, mass attenuation coefficient and half-value layer using a wide range of gamma-rays energies 356, 511, 662, 1173, 1274 and 1332 keV, were determined. Transmitted gamma rays were measured by NaI(Tl) scintillation detector. Mass attenuation coefficients of the prepared composites samples have been measured experimentally and compared theoretically by XCOM, reasonable agreement has been observed. Also, the attenuation of the transmitted collimated thermal neutrons emitted from Californium-252 neutron source was measured using BF3 detector. The measured macroscopic cross-section of transmitted thermal neutron indicated that composites Lead borate glass and unglazed ceramic with the highest percentage of Boron and Barium, respectively are more effective than lower percentages as a thermal neutrons shield. The measured and calculated mass attenuation coefficient for gamma rays indicated that Lead borate glass and unglazed ceramic composites with the highest percentage of Lead are more effective than lower percentage against gamma-rays. Highlights for Reviewers: Different percentages Pb & Ba added to unglazed ceramic for special applications. The capability of using LBG & UC composites as a radiation shielding was evaluated. LBG & UC used against gamma rays and thermal neutrons for radiotherapy facilities. UC composites with 15% Pb and 15% Ba additives are quite good radiation shields. Values of ( μ ρ ) and HVL for LBG & UC were compared with other shielding materials.